2022
DOI: 10.1002/trtr.2097
|View full text |Cite
|
Sign up to set email alerts
|

Taking the Leap: Supporting Multilingual Writers Through Translanguaging

Abstract: Translanguaging pedagogies support student writers in expressing themselves using their full language repertoires, writing for authentic audiences, and connecting to their identities. However, many teachers, particularly those who identify as “monolingual” and teach in English‐medium classrooms, may not know how to introduce translanguaging into their writing instruction. This study explores how three pre‐service teachers enrolled in a writing methods course enacted translanguaging pedagogies in their English‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Roundy and Roundy (2009), in their study investigating the effect of repeated reading on the development of fluent reading, found that the repeated reading strategy increased the students' reading speed. Many studies have been conducted using repeated reading which is one of the oldest and the most effective methods (Akyol & Çetinkaya, 2009;Akyol & Ketenoğlu Kayabaşı, 2018;Carver & Hoffman, 1981;Gonzales & Elijah, 1975;O'Shea, Sinderal & O'Shea, 1987;Özkara, 2010;Weinstein, 2004;Yıldız, 2013;Yılmaz, 2008). The findings reported by these studies concur with the finding of the current study.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Roundy and Roundy (2009), in their study investigating the effect of repeated reading on the development of fluent reading, found that the repeated reading strategy increased the students' reading speed. Many studies have been conducted using repeated reading which is one of the oldest and the most effective methods (Akyol & Çetinkaya, 2009;Akyol & Ketenoğlu Kayabaşı, 2018;Carver & Hoffman, 1981;Gonzales & Elijah, 1975;O'Shea, Sinderal & O'Shea, 1987;Özkara, 2010;Weinstein, 2004;Yıldız, 2013;Yılmaz, 2008). The findings reported by these studies concur with the finding of the current study.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…García and Kleifgen (2020) encourage adopting a multimodal translanguaging perspective that brings MLs from the margins of literacy knowledge to the center with their metalinguistic abilities to think critically about texts, language, audiences, and purposes. In navigating social hierarchies, encouraging full linguistic use through translanguaging can build student confidence in writing and disrupt the positioning of MLs as deficient (García & Kleifgen, 2020; Gonzales & Machado, 2022).…”
Section: Perspectivesmentioning
confidence: 99%